Maintenance of Hypoimmunogenic Features via Regulation of Endogenous Antigen Processing and Presentation Machinery - An, Ju-Hyun; Koh, Hyebin; Ahn, Yujin; Kim, Jieun; Han, A-Reum; Lee, Ji Yoon; Kim, Sun-Uk; Lee, Jong-Hee (Frontiers in Bioengineering and Biotechnology, 2022)
Universally acceptable donor cells provide immunotypically matched materials for regenerative medicine. Because forced expression of hypoimmunogenic genes represses the immune response, we established universal pluripotent stem cells (PSCs) by replacing endogenous β2-microglobulin (β2m) with β2m directly conjugated to human leukocyte antigen (HLA)-G, thereby simultaneously suppressing HLA-I expression and the natural killer (NK) cell-mediated immune response. These modified human PSCs retained their pluripotency and differentiation capacity; however, surface presentation of HLA-G was absent from subsequently differentiated cells, particularly cells of neural lineages, due to downregulation of antigen-presentation machinery (APM) genes. Induction of APM genes by overexpression of NLR-family CARD domain-containing 5 (NLRC5) or activator subunit of nuclear factor kappa B (NF-κB) heterodimer (RelA), recovered the surface expression of HLA-G and the hypoimmunogenicity of neural cells. Our findings enhance the utility of hypoimmunogenic cells as universal donors and will contribute to the development of off-the-shelf stem-cell therapeutics.